Expressão gráfica arquitetônica: um estudo sobre a relação entre os sujeitos, o meio e a produção acadêmica na construção do conhecimento - Fulgêncio, Vinicius Albuquerque (2021)
This research aims at investigating knowledge construction within the academic field of Graphic Expression (also known as Graphic Design or Technical Drawing). The literature portrays the field as lacking an identity, as being intuitive and lacking theoretical-methodological rigour, and as focusing on technologies instead of teaching-learning processes. To verify these claims, this thesis investigates the relationship between academia and its subjects, as well as the relationship between academic production and subjects, using Graphic Education and the Teaching of Architectural Graphic Expression as a framework. Advances in an area of knowledge presuppose that its results are based on a theoretical-methodological structure. In this research, the academia are departments and graduate courses (M.Sc. and PhD research programs) and the subjects are teachers' curricula. To study what kind of knowledge these relationships build and validate, the research analyses publications of two congresses in Graphic Expression. This work is characterized by a case study, seeking to understand the relationships between cases and context. From the theoretical contributions, analytical categories were developed to understand the relationships between the academia and subjects, as well publications and subjects. The results demonstrate that having a specific academic environment for Graphic Expression does not result into an academic production directed to the field, whether at undergraduate or graduate level. The Graphic Expression identity is diffuse, but it has two main parts: geometry and image studies. The Architectural Graphics Expression, within the scope of this research, presents an academic production directed to the field, even though it does not find a place within graduate programs in Architecture and Urbanism. Finally, academic production on the Teaching of Architectural Graphic Expression presents problems of a theoretical-methodological nature, but there are signs of improvement in recent years.